Madness, magic, and medicine : the treatment and mistreatment of the mentally ill - Horwitz, Elinor Lander, 1929- (Philadelphia : Lippincott, 1977)
Discusses the treatment of the mentally ill through the ages.
Includes index.
Bibliography: p. [185]-187.
Keywords: Mental disorders -- History; Mental disorders -- Therapy; Mentally ill -- Care -- History -- Juvenile literature; Mentally ill -- Care -- History